The Impact of Soft Law on Legal Consequences for AI System Providers within the Framework of the Artificial Intelligence Act - Kunstek, Natalija (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
The regulation of European legislation is moving towards the protection of users of artificial intelligence (AI) systems in such a way that AI system providers are required to categorize their systems into an appropriate risk class, as defined under the Artificial Intelligence Act. This classification enables the user to define the risks they face when using a specific AI system. The implementation of the Act in individual cases is prescribed by the European Commission's Guidelines. This chapter, focusing on the influence of the European Commission’s Guidelines on the enforcement of the Artificial Intelligence Act, addresses the question of whether the Guidelines affect the imposition of penal provisions as stipulated by the Act for AI system providers. Furthermore, it analyzes the impact of "soft law," such as rulings from the tax authority, and other writings in Slovenia, and their effect on the implementation of the Act.